Heat Flux Based Optimization of Combined Heat and Power Thermoelectric Heat Exchanger - Kazuaki Yazawa (MDPI AG, 2021)
We analyzed the potential of thermoelectrics for electricity generation in a combined heat and power (CHP) waste heat recovery system. The state-of-the-art organic Rankine cycle CHP system provides hot water and space heating while electricity is also generated with an efficiency of up to 12% at the MW scale. Thermoelectrics, in contrast, will serve smaller and distributed systems. Considering the limited heat flux from the waste heat source, we investigated a counterflow heat exchanger with an integrated thermoelectric module for maximum power, high efficiency, or low cost. Irreversible thermal resistances connected to the thermoelectric legs determine the energy conversion performance. The exit temperatures of fluids through the heat exchanger are important for the system efficiency to match the applications. Based on the analytic model for the thermoelectric integrated subsystem, the design for maximum power output with a given heat flux requires thermoelectric legs 40–70% longer than the case of fixed temperature reservoir boundary conditions. With existing thermoelectric materials, 300–400 W/m2 electrical energy can be generated at a material cost of $3–4 per watt. The prospects of improvements in thermoelectric materials were also studied. While the combined system efficiency is nearly 100%, the balance between the hot and cold flow rates needs to be adjusted for the heat recovery applications.